Trenches apart, yet worm to worm: inter- and intra-trench comparisons reveal divergent and convergent dynamics in hadal nematode biodiversity - Yick Hang Kwan; Sofie Derycke; Blandine Trouche; Frank Wenzhöfer; Mathias Middelboe; Angelika Brandt; Mauricio Shimabukuro; Ronnie N. Glud; Daniela Zeppilli (Progress in Oceanography, 2025)

The influence of habitat heterogeneity and disturbance on benthic community structure in deep-sea polymetallic nodule environments and management implications for seabed mining - Ailish Ullmann; Ashley A. Rowden; Daniel Leduc; Daniela Zeppilli (Frontiers in Marine Science, 2025)
Habitat heterogeneity is known to influence faunal community structure, but its influence on deep-sea benthic communities remains understudied, particularly for polymetallic nodule environments in abyssal waters. As nodules are currently of interest for mining, understanding the potential impact of this disturbance on habitat heterogeneity, and the subsequent effect on faunal communities, becomes critical for developing environmental management plans. Although some aspects of the influence of habitat heterogeneity on the nodule-associated fauna have been studied, the influence on multiple size components of the benthic community across varying spatial scales has not yet been fully assessed, and the current metrics by which habitat heterogeneity is measured may be insufficient. This review synthesizes existing research regarding habitat heterogeneity, the influence of disturbance on habitat heterogeneity, and the influence of this heterogeneity on metazoan fauna (megafauna, macrofauna, and meiofauna) in polymetallic nodule environments across spatial scales. Current gaps in knowledge and the implications of this knowledge for the management of proposed deep-seabed mining are also discussed.

Discovery of a new Kinorhyncha species from the uncharted South Orkney Trench (Southern Ocean) - Nuria Sánchez; Marta García-Cobo; Mauricio Shimabukuro; Daniela Zeppilli; Hidetaka Nomaki; Alberto González-Casarrubios (Zoologischer Anzeiger, 2024)

Deciphering environmental forcings in the distribution of meiofauna and nematodes in mangroves of the Atlantic-Caribbean-East Pacific and Indo-West Pacific regions - Adriana Spedicato; Daniela Zeppilli; Gérard Thouzeau; Philippe Cuny; Cécile Militon; Léa Sylvi; Cédric Hubas; Guillaume Dirberg; Ronan Jézéquel; Guerric Barrière; Loïc N. Michel; Tânia Nara Bezerra; et al. (Science of The Total Environment, 2024)

Industrial mining trial for polymetallic nodules in the Clarion-Clipperton Zone indicates complex and variable disturbances of meiofaunal communities - Nene Lefaible; Lara Macheriotou; Ellen Pape; Massimiliano Molari; Matthias Haeckel; Daniela Zeppilli; Ann Vanreusel (Frontiers in Marine Science, 2024)
Following several small-scale benthic disturbance experiments, an industrial polymetallic nodule collector trial was conducted by the company Global Sea mineral Resources (GSR) in their exploration contract area in the Clarion-Clipperton Zone using the pre-prototype vehicle Patania II (PATII). In this study, meiofaunal (i.e., nematode abundance, ASV diversity and genus composition) and environmental (i.e., grain size, total organic carbon/total nitrogen and pigment) properties are compared between disturbance categories (i.e., Pre-impact, Collector Impact and Plume Impact). One week after the trial, proxies for food availability within the Collector Impact sediments were altered with lower total organic carbon (TOC) and pigment (i.e., CPE: sum of Chlorophyll a and phaeopigments) values. Albeit not significant, the observed decrease of nematode abundance and ASV diversity, further indicate the consequences of the removal of the ecologically important surface sediment layer within the PATII tracks. Next to sediment removal, exposed sediments were modified in different ways (e.g., central strips, parallel caterpillar imprints with alternating bands of depressions/ripples and interface patches) and were also subject to heavy collector-induced sediment blanketing. We propose that these cumulative impacts have led to intricate seabed modifications with various levels of disturbance intensity which resulted in the high meiofaunal variability observed. Adjacent nodule-rich areas (i.e., Plume Impact) received considerable levels of sediment deposition (2-3 cm) and were defined by significantly lower food sources (CPE, TOC, carbon to nitrogen ratio) and an observation of meiofaunal enrichment (i.e., higher average nematode abundance and ASV diversity; although statistically non-significant), but mechanisms behind these ecological changes (e.g., suspended material-surface fluxes, passive dispersal of fauna in the plume vs. active upward migration and “viability” of redeposited fauna) remain unresolved. We conclude that complex benthic pressure-response relationships associated with the PATII trial, combined with the high degree of natural spatial and temporal variability in abyssal meiofaunal communities and sedimentary parameters, complicates the quantitative assessment of deep-sea mining associated disturbances.

The first deep-sea ctenostome bryozoan from the Indian Ocean: Aethozoon flavum sp. nov. - Thomas Schwaha; Daniela Zeppilli; Alberto González-Casarrubios; Diego Cepeda (Marine Biodiversity, 2024)
Aethozoid ctenostome bryozoans are an unusual, small group of solitary ctenostome bryozoans, occurring almost exclusively in deep-sea habitats. Currently, there are only five species belonging to four, still insufficiently known genera, which have been reported from the Atlantic and Pacific Oceans. Recent examination of sediment core samples from an active volcanic area near Mayotte revealed a high abundance of aethozoids, recorded for the first time in the Indian Ocean. A comparative approach identified the specimens as belonging to a new species, Aethozoon flavum sp. nov. There are particular characters diagnostic of this new species, such as basally oriented duplicature bands, a highly denticulate proximal vestibular wall, and a highly elongated anal tube terminating in an almost vestibular anus. This species is the first ctenostome observed at depths of over 3.000 m in the Indian Ocean. Morphological characters are compared among all aethozoids, but still require more detailed analyses in most species. Aethozoids appear to be globally distributed and often occur in high numbers, which indicates that additional efforts will increase their distribution and species range. Ultimately, additional studies will be able to show the ecological importance of these bryozoans and molecular studies should reveal more about their diversity and phylogenetic affinities.

Environmental drivers modelling the mangrove Kinorhyncha community along an urban-to-natural gradient in French Guiana (western Atlantic Ocean) - Diego Cepeda; Nuria Sánchez; Adriana Spedicato; Emma Michaud; Daniela Zeppilli (Frontiers in Marine Science, 2024)
Meiofaunal communities are dominated by free-living nematodes and harpacticoid copepods. Most of the studies defining the environmental drivers that influence meiofauna focus on these profuse groups. The ‘rare’ meiofaunal organisms (densities <5%) are frequently overlooked, making it difficult to know which abiotic variables influence their populations, or their ecological role in the benthic ecosystems. In this study, we explore the ecological factors that characterize a low human-polluted mangrove in French Guiana (western Atlantic Ocean) along an urban-to-natural gradient, focusing on the ‘rare’ phylum Kinorhyncha. This taxon seems to be mainly influenced by sediment size, being more abundant in silty sediments. The presence of microorganisms also enhances the community, likely due to a higher food availability. Oppositely, some trace metals of both lithogenic and anthropogenic origin, as well as predominance of coarser sediment particles, seem to negatively affect their populations. The importance of including the lesser abundant groups of meiofauna in ecological studies is evident, since it allows to have a better idea of the ecological state of marine benthic environments.

Editorial: 16th deep-sea biology symposium - Alexandra Anh-Thu Weber; Paris V. Stefanoudis; Daniela Zeppilli; Eleonora Puccinelli (Frontiers in Marine Science, 2023)

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Digging deep: lessons learned from meiofaunal responses to a disturbance experiment in the Clarion-Clipperton Zone - Nene Lefaible; Lara Macheriotou; Kaveh Purkiani; Matthias Haeckel; Daniela Zeppilli; Ellen Pape; Ann Vanreusel (Marine Biodiversity, 2023)
The deep-sea mining industry is currently at a point where large-sale, commercial polymetallic nodule exploitation is becoming a more realistic scenario. At the same time, certain aspects such as the spatiotemporal scale of impacts, sediment plume dispersion and the disturbance-related biological responses remain highly uncertain. In this paper, findings from a small-scale seabed disturbance experiment in the German contract area (Clarion-Clipperton Zone, CCZ) are described, with a focus on the soft-sediment ecosystem component. Despite the limited spatial scale of the induced disturbance on the seafloor, this experiment allowed us to evaluate how short-term (< 1 month) soft-sediment changes can be assessed based on sediment characteristics (grain size, nutrients and pigments) and metazoan meiofaunal communities (morphological and metabarcoding analyses). Furthermore, we show how benthic measurements can be combined with numerical modelling of sediment transport to enhance our understanding of meiofaunal responses to increased sedimentation levels. The lessons learned within this study highlight the major issues of current deep-sea mining-related ecological research such as deficient baseline knowledge, unrepresentative impact intensity of mining simulations and challenges associated with sampling trade-offs (e.g., replication).

The diversification of the antimicrobial peptides from marine worms is driven by environmental conditions - Renato Bruno; Céline Boidin-Wichlacz; Oleg Melnyk; Daniela Zeppilli; Céline Landon; Frédéric Thomas; Marie-Anne Cambon; Mickael Lafond; Kamel Mabrouk; François Massol; Stéphane Hourdez; Marc Maresca; et al. (Science of The Total Environment, 2023)

Nematode diversity patterns in mangroves: a review of environmental drivers at different spatial scales - Adriana Spedicato; Daniela Zeppilli; Gérard Thouzeau; Emma Michaud (Biodiversity and Conservation, 2023)

Hybrid conferences: opportunities, challenges and ways forward - Eleonora Puccinelli; Daniela Zeppilli; Paris V. Stefanoudis; Annaïg Wittische-Helou; Marjorie Kermorgant; Sandra Fuchs; Lénaïck Menot; Erin E. Easton; Alexandra A-T. Weber (Frontiers in Marine Science, 2022)
Hybrid conferences are in-person events that have an online component. This type of meeting format was rare before the COVID-19 pandemic, but started to become more common recently given the asynchronous global progression of the pandemic, the uneven access to vaccines and different travel regulations among countries that led to a large proportion of participants being unable to attend conferences in person. Here we report the organization of a middle-sized (581 participants: 159 onsite, 422 online) international hybrid conference that took place in France in September 2021. We highlight particular organizational challenges inherent to this relatively new type of meeting format. Furthermore, we surveyed both in-person and online participants to better understand their conference experience and to propose improvements based on the feedback received. Finally, we compare the advantages and disadvantages of three types of conferences (onsite-only, online-only and hybrid) and suggest that hybrid events should be favored in the future because they offer the most flexibility to participants. We conclude by proposing suggestions and ways forward to maximize accessibility and inclusivity of hybrid conferences. Our study brings novel insights on the challenges and opportunities created by hybrid conferences, by reporting not only the organizing committee experience but also by considering the participants’ perspective.

Hadal Mud Dragons: First Insight Into the Diversity of Kinorhyncha From the Atacama Trench - Katarzyna Grzelak; Daniela Zeppilli; Mauricio Shimabukuro; Martin V. Sørensen (Frontiers in Marine Science, 2021)
Deep-sea trenches are one of the last frontiers for deep-sea exploration and represent a large reservoir of undiscovered biodiversity. This applies in particular to organisms belonging to smaller-size classes, such as meiofauna. Among different meiofauna taxa, kinorhynchs represent a large gap in our knowledge about global marine biodiversity in general, but primarily in extreme deep-sea environments. Out of the more than 300 known mud dragon species, only a single species has ever been described from hadal depths (> 6000 m), i.e., Echinoderes ultraabyssalis from the Kuril-Kamchatka Trench. The results presented in this paper are based on material collected during a research expedition in 2018 investigating the Atacama Trench environment. We provide a first overview and comparison of the diversity and abundance of mud dragons in the Atacama Trench, the adjacent abyssal plain and continental slope off Chile. The study revealed six species of Echinoderes . Of these, Echinoderes mamaqucha sp. nov. is described as a new species and morphological data of three undescribed species are given. Because of the low number of available specimens, we provide only a brief description of these three species and comparison with their morphologically closest congeners, but formal descriptions are not given. Moreover, Echinoderes juliae and Echinoderes pterus were also recovered. Echinoderes juliae was described from the abyssal plain off Oregon and along the continental rise off California, at 2702 to 3679 m depth. Echinoderes pterus is known from the high Arctic, the North Atlantic, and the Mediterranean Sea, and has also been reported to show a wide bathymetric distribution, from 675 to 4403 m. Interestingly, E. mamaqucha sp. nov. dominated at the trench stations and it reached its highest abundance at the deepest station, at 8085 m water depth. The only other single individual that was found in the Atacama Trench was Echinoderes sp.1. The remaining four species were all found at the abyssal and slope stations. The obtained results seem to confirm previous hypotheses about geographic isolation of deep-sea trenches and relatively low connectivity with other habitats, reflected by limited diversity of sediment dwelling fauna, particularly in the deepest parts of trenches.

Corrigendum: Deep-Sea Nematodes of the Mozambique Channel: Evidence of Random Community Assembly Dynamics in Seep Sediments - Lara Macheriotou; Annelien Rigaux; Karine Olu; Daniela Zeppilli; Sofie Derycke; Ann Vanreusel (Frontiers in Marine Science, 2021)

Deep-Sea Nematodes of the Mozambique Channel: Evidence of Random Community Assembly Dynamics in Seep Sediments - Lara Macheriotou; Annelien Rigaux; Karine Olu; Daniela Zeppilli; Sofie Derycke; Ann Vanreusel (Frontiers in Marine Science, 2021)
Cold seeps occur globally in areas where gases escape from the seafloor, occasionally resulting in the formation of topographic depressions (pockmarks), characterised by unique physicochemical conditions such as anoxic and sulphuric sediments. Free-living marine nematodes tend to dominate the meiofaunal component in such environments, often occurring at extremely high densities and low richness; the mechanisms defining community assembly in areas of fluid seepage, however, have received little attention. Here we focus on a low-activity pockmark at 789 m in the Mozambique Channel (MC). We assessed the diversity, co-occurrence patterns and phylogenetic community structure of nematodes at this bathyal site to that of a nearby reference area as well as abyssal sediments using metabarcoding. In addition, we compared our molecularly-derived diversity estimates to replicate samples identified morphologically. Overall, nematode Amplicon Sequence Variants (ASVs) and generic richness were similar between Pockmark and Abyssal sediments, but lower compared to the Reference area. Although more than half the genera were shared, over 80% of ASVs were unique within each area and even within each replicate core. Even though both methodologies differentiated the Pockmark from the Reference and Abyssal sites, there was little overlap between the molecularly and morphologically identified taxa, highlighting the deficit of reference sequences for deep-sea nematodes in public databases. Phylogenetic community structure at higher taxonomic levels was clustered and did not differ between the three areas yet analysis within three shared and dominant genera ( Acantholaimus, Desmoscolex, Halalaimus ), revealed randomness with respect to phylogeny as well as co-occurrence which was exclusive to the Pockmark area. These patterns point to the influence of neutral dynamics at this locality resulting from the stochastic sampling of early colonizing taxa, the successional stage at sampling and/or the functional redundancy within the investigated genera.

Editorial: Extreme Benthic Communities in the Age of Global Change - Roberto Sandulli; Jeroen Ingels; Daniela Zeppilli; Andrew Kvassnes Sweetman; Sarah Hardy Mincks; Furu Mienis; Wei Chin-Lin (Frontiers in Marine Science, 2021)

Dragons of the Deep Sea: Kinorhyncha Communities in a Pockmark Field at Mozambique Channel, With the Description of Three New Species - Diego Cepeda; Fernando Pardos; Daniela Zeppilli; Nuria Sánchez (Frontiers in Marine Science, 2020)

First report of nematocysts fired at deep-sea hydrothermal vent nematodes - Daniela Zeppilli; Stefania Puce (Marine Biodiversity, 2020)

An Assessment of Environmental Metabarcoding Protocols Aiming at Favoring Contemporary Biodiversity in Inventories of Deep-Sea Communities - Miriam I. Brandt; Blandine Trouche; Nicolas Henry; Cathy Liautard-Haag; Lois Maignien; Colomban de Vargas; Patrick Wincker; Julie Poulain; Daniela Zeppilli; Sophie Arnaud-Haond (Frontiers in Marine Science, 2020)

Meiofauna Community in Soft Sediments at TAG and Snake Pit Hydrothermal Vent Fields - Adriana Spedicato; Nuria Sánchez; Lucie Pastor; Lenaick Menot; Daniela Zeppilli (Frontiers in Marine Science, 2020)

Environmental and Benthic Community Patterns of the Shallow Hydrothermal Area of Secca Delle Fumose (Baia, Naples, Italy) - Luigia Donnarumma; Luca Appolloni; Elena Chianese; Renato Bruno; Elisa Baldrighi; Rosanna Guglielmo; Giovanni F. Russo; Daniela Zeppilli; Roberto Sandulli (Frontiers in Marine Science, 2019)

Biodiversity and ecology of meiofauna in extreme and changing environments - Daniela Zeppilli; Daniel Leduc (Marine Biodiversity, 2018)

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

Colonization of synthetic sponges at the deep-sea Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge): a first insight - Elisa Baldrighi; Daniela Zeppilli; Rosalie Crespin; Pierre Chauvaud; Florence Pradillon; Jozée Sarrazin (Marine Biodiversity, 2018)

Meiofauna international workshop “MeioScool 2013: a dive into a microscopic world” - Daniela Zeppilli; Jozée Sarrazin (Marine Biodiversity, 2015)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Rapid colonisation by nematodes on organic and inorganic substrata deployed at the deep-sea Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) - Daniela Zeppilli; Ann Vanreusel; Florence Pradillon; Sandra Fuchs; Perrine Mandon; Tristan James; Jozée Sarrazin (Marine Biodiversity, 2015)

A new species of Neostygarctus (Arthrotardigrada) from the Condor Seamount in the Azores, Northeast Atlantic - Reinhardt Møbjerg Kristensen; Martin Vinther Sørensen; Jesper Guldberg Hansen; Daniela Zeppilli (Marine Biodiversity, 2015)

The contribution of deep‐sea macrohabitat heterogeneity to global nematode diversity - Ann Vanreusel; Gustavo Fonseca; Roberto Danovaro; Maria Cristina Da Silva; André M. Esteves; Tim Ferrero; Gunnar Gad; Valentina Galtsova; Cristina Gambi; Veronica Da Fonsêca Genevois; Jeroen Ingels; Baban Ingole; et al. (Marine Ecology, 2010)
The great variety of geological and hydrological conditions in the deep sea generates many different habitats. Some are only recently explored, although their true extent and geographical coverage are still not fully established. Both continental margins and mid‐oceanic seafloors are much more complex ecologically, geologically, chemically and hydrodynamically than originally thought. As a result, fundamental patterns of species distribution first observed and explained in the context of relatively monotonous slopes and abyssal plains must now be re‐evaluated in the light of this newly recognized habitat heterogeneity. Based on a global database of nematode genus composition, collected as part of the Census of Marine Life, we show that macrohabitat heterogeneity contributes significantly to total deep‐sea nematode diversity on a global scale. Different deep‐sea settings harbour specific nematode assemblages. Some of them, like coral rubble zones or nodule areas, are very diverse habitats. Factors such as increased substrate complexity in the case of nodules and corals seem to facilitate the co‐existence of a large number of genera with different modes of life, ranging from sediment dwelling to epifaunal. Furthermore, strong biochemical gradients in the case of vents or seeps are responsible for the success of particular genera, which are not prominent in more typical soft sediments. Many nematode deep‐sea genera are cosmopolitan, inhabiting a variety of deep‐sea habitats and oceans, whereas only 21% of all deep‐sea genera recorded are restricted to a single habitat. In addition to habitat heterogeneity, regional differences are important in structuring nematode assemblages. For instance, seeps from different regions yield different genera that thrive on the sulphidic sediments. This study also shows that many areas and habitats remain highly under‐sampled, affecting our ability to understand fully the contribution of habitat heterogeneity versus regional differences to global nematode diversity.